The Cold Heart: Reminders of Money Cause Feelings of Physical Coldness. (July 2015) - Reutner, Leonie; Hansen, Jochim; Greifeneder, Rainer
Mere reminders of money have been shown to cause socially "cold" behavior. Recent research suggests that the metaphor of "social coldness" is bodily grounded and thus linked to actual sensations of physical coldness. We therefore hypothesized that reminding individuals of money causes them to feel physically colder. This hypothesis was put to test in two studies, drawing on predictions from psychophysiological thermal perception. In Study 1, individuals who had been reminded of money perceived the air in the room as colder compared to a control group (an assimilation effect). Contrarily, in Study 2, they perceived water (a medium that was only momentarily experienced) as warmer compared to individuals not reminded of money (a contrast effect). Together these findings demonstrate that reminders of money cause sensations of actual physical coldness and add to the literature of both the psychological effects of money and human thermal perception.